Local Wisdom of Stablean Hamlet Community as a Form of Preparedness in Facing Volcanic Eruption Disasters - Dwi Intan Rahmawati; Heri Irawan; Ni’maturrodhiyah Ni’maturrodhiyah; Tiesya Valvina Pramaysela; Pradika Adi Wijayanto; Andhika Rizqy Heristama (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
Mount Merapi, Indonesia's most active volcano, poses significant threats to the Stabelan Hamlet situated nearby. This study delves into the community's indigenous knowledge, residing about 3 km from Mount Merapi's summit, in confronting volcanic eruption disasters. Employing qualitative methods, the research elucidates local customs and ancestral beliefs crucial for disaster readiness. Interviews provide primary data, complemented by secondary sources like journals and news. Employing purposive sampling, data analysis follows the Miles and Huberman model. Findings reveal the Stabelan Hamlet's adeptness in employing local wisdom like creating bonfires, maintaining calm during eruptions, and interpreting dreams as disaster coping mechanisms. This indigenous wisdom not only shapes preparedness but also preserves cultural heritage local wisdom, The community's receptiveness ensures the integration of traditional practices alongside contemporary disaster management strategies mandated by the government.